Mixed solder paste applied to photovoltaic junction box and application method of mixed solder paste
By using mixed tin paste in the welding of photovoltaic wiring boxes, the tin alloy powder with different melting points is used to form a stable solder joint at low temperature to solve the problem of low existing process efficiency, and the stability and efficiency of welding are achieved.
Patent Information
- Application Number
- CN202411738374.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-29
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2044-11-29
AI Technical Summary
The existing photovoltaic junction box welding process is long, slow, and reduced efficiency.
The use of a mixed tin paste, including SN63PB37 powder and tinyl alloy powder, promotes low temperature at low temperature heating to form a initial solder point first, and uses the second welding of unpolished high temperature.
Stable and reliable solder joints are formed at low temperatures, reducing the deformation and residual pollution of the solder joints, and improving the welding efficiency and firmness.
Smart Images

Figure BDA0005162025190000061
Abstract
Description
Technical Field
[0001] The present application relates to the field of photovoltaic junction box welding, and in particular to a mixed solder paste applied to a photovoltaic junction box and an application method thereof. Background Art
[0002] With the rapid development of the photovoltaic industry in recent years, the demand for photovoltaic modules has also increased significantly. The main function of the solar photovoltaic junction box is to connect and protect solar photovoltaic modules, connect the power generated by solar cells to external lines, and conduct the current generated by photovoltaic modules. Therefore, the firmness of the photovoltaic junction box welding is crucial to the stable transmission of current. By 2023, it is estimated that the output value of solder paste used for each GW photovoltaic junction box is about 1 million.
[0003] However, the current production of photovoltaic junction boxes mainly involves first applying a small amount of solder paste or glue and then welding the soldering pieces. The components will then be sent to the component factory for hot pressing and soldering reflow tape. The existing process involves applying solder paste, pasting solder pieces, welding, and welding the busbars at the component factory. The process is long, slow, and inefficient. Summary of the invention
[0004] In order to improve the existing photovoltaic junction box welding process, the present application provides a mixed solder paste applied to a photovoltaic junction box and an application method thereof.
[0005] In a first aspect, the present application provides a mixed solder paste for use in a photovoltaic junction box, which adopts the following technical solution: a mixed solder paste for use in a photovoltaic junction box, comprising a mixed tin powder and a soldering paste, wherein the mixed tin powder comprises Sn 63 Pb 37 powder and tin-bismuth alloy powder, wherein the tin-bismuth alloy is Sn 69.5 Bi 30 Cu 0.5 and Sn 64 Bi 35 Ag 1 One of the Sn 63 Pb 37 The mass ratio of tin-bismuth alloy powder to tin-bismuth alloy powder is (3-6):1.
[0006] By adopting the above technical solution, Sn 63 Pb 37 The melting point of the alloy powder is about 183°C. 69.5 Bi 30 Cu 0.5 and Sn 64 Bi 35 Ag 1The melting point is 138-187℃. A mixed solder paste is made by mixing two alloys with large melting point differences. The low-temperature phase is used in a small amount. Low-temperature heating can cause the solder joint to be initially formed when the low-temperature phase melts first, making the solder joint hard and firm. The unmelted high-temperature phase is used to heat the solder piece to achieve secondary welding, and the solder strip is firmly welded.
[0007] By Sn 63 Pb 37 The melting point of the mixed tin powder formed by the powder and the tin-bismuth alloy powder is about 175.5, which enables the mixed solder paste prepared in the present application to be heated at a low temperature of 170-200°C to form solder joints, and the solder joints are stable and reliable, not easy to deform, the solder joints are of moderate size, and the residual pollution is low. At the same time, the residual solder pieces can provide the required flux for secondary welding, and can be firmly welded to the solder strip under high temperature heating.
[0008] Adding bismuth powder to tin powder can reduce the melting point of the mixed solder paste and make the mixed solder paste have better fluidity. At the same time, adding a small amount of Ag to the tin-bismuth alloy powder can refine the grains, improve the strength of the solder joints, and reduce the phenomenon of black solder joints caused by Bi surface enrichment and oxidation.
[0009] Preferably, the mass ratio of the mixed tin powder to the soldering solder paste is 100:(10-13).
[0010] Preferably, the particle size of the tin powder in the mixed tin powder is 25-53 μm.
[0011] Preferably, the soldering paste comprises the following raw materials in parts by weight: 40-50 parts of solvent, 30-40 parts of rosin resin, 1-3 parts of hydrogenated castor oil, 1-3 parts of fumed silica, and 5-10 parts of activator.
[0012] By adopting the above technical solution, rosin resin can play a role of bonding and protection during the welding process, increase the viscosity of the mixed solder paste, help the solder to be fixed on the welding point, and form a protective film after welding to prevent oxidation and corrosion of the solder joint, thereby improving the reliability and stability of the solder joint. Hydrogenated castor oil can reduce the surface tension of the solder, promote the flow and wetting of the mixed solder paste on the welding point, and improve the welding quality and efficiency. At the same time, hydrogenated castor oil also has certain antioxidant properties, which helps to protect the solder joint from oxidation. Fumed silica can adjust the viscosity and thixotropy of the solder paste, prevent the solder paste from settling and stratification during storage and use, and ensure the stability and printing performance of the solder paste.
[0013] Preferably, the solvent is at least one of polyethylene glycol, ethylene glycol, tetrahydrofurfuryl alcohol, hydrogenated rosin propyl ether, and diethyl adipate.
[0014] Preferably, the active agent is at least one of methylsuccinic acid, oxalic acid, salicylic acid and succinic acid.
[0015] By adopting the above technical solution, methylsuccinic acid, oxalic acid, salicylic acid and succinic acid can remove oxides and pollutants on the surface of the solder joint, reduce the surface tension of the solder, and promote the wetting and bonding of the solder and the substrate. The activator can improve the reliability of welding and the strength of the solder joint and reduce welding defects.
[0016] In a second aspect, the present application provides a method for applying a mixed solder paste applied to a photovoltaic junction box, using the following technical solution: A method for applying a mixed solder paste for a photovoltaic junction box comprises the following specific steps: uniformly mixing mixed tin powder and flux paste, vacuumizing and shaping to form a mixed solder paste, applying the mixed solder paste on a concave substrate for printing, then soldering at 170-200°C for 35-45s without applying pressure in an air atmosphere, and finally cooling to room temperature.
[0017] By adopting the above technical solution, the mixed solder paste can be preformed in an air atmosphere, and a preformed solder sheet can be formed by printing and baking at a low temperature, which saves the solder sheet patch welding process, the solder joint size is moderate, the solder sheet strength meets the standard, the viscosity is strong and not easy to fall off, the auxiliary pollution is low, and the residual solder sheet can provide the flux required for secondary welding, which can be firmly welded to the busbar under high temperature heating. The use of a concave substrate can reduce the printing amount of solder paste without reducing the thickness of the solder joint, making the solder joint smaller and avoiding the overflow of the solder joint.
[0018] Preferably, the rosin resin is heated and dissolved, and then a solvent, hydrogenated castor oil, fumed silica, and an activator are added and mixed evenly to obtain a solder paste; the mixed tin powder and the solder paste are mixed evenly, and the mixed solder paste is formed after vacuuming to form a mixed solder paste; the mixed solder paste is applied to a concave substrate for printing, and then soldered at 170-200° C. for 35-45 seconds without applying pressure in an air atmosphere, and finally cooled to room temperature.
[0019] In summary, this application has the following beneficial effects: 1. Since this application uses Sn 63 Pb 37 Sn 69.5 Bi 30 Cu 0.5 Sn 64 Bi 35 Ag 1 Mixed with flux paste to form a mixed solder paste, it can be heated at low temperature, so that the low temperature phase melts first and the solder joints are formed for the first time, making the solder joints stable and reliable. At the same time, the unmelted high temperature phase is used to heat the solder piece to achieve secondary welding, and the solder strip is firmly welded.
[0020] 2. In this application, preformed solder sheets are formed by low-temperature baking through printing, so that the solder sheets have higher strength and are not easy to fall off. The remaining solder sheets can provide flux for secondary welding. The original process of applying solder paste / glue and then sticking the solder sheets is changed by printing mixed solder paste, which optimizes the process, saves time and increases efficiency. DETAILED DESCRIPTION
[0021] The present application is further described in detail below with reference to the embodiments.
[0022] All raw materials in the examples are commercially available. Example
[0023] Example 1 This embodiment provides a mixed solder paste for a photovoltaic junction box, including mixed tin powder and solder paste, wherein the mass ratio of the mixed tin powder to the solder paste is 100:11.5, and the mixed tin powder includes Sn 63 Pb 37 Powder and Sn 69.5 Bi 30 Cu 0.5 , Sn 63 Pb 37 Powder and Sn 69.5 Bi 30 Cu 0.5 The mass ratio of Sn is 5:1. 63 Pb 37 Sn 63 Pb 37 -T3E type, Sn 69.5 Bi 30 Cu 0.5 Sn 69.5 Bi 30 Cu 0.5 -T3 type, the average particle size of the mixed tin powder is 25-53μm, and the solder paste includes the following raw materials in parts by weight: 45kg of solvent and 35kg of rosin resin, wherein the solvent is ethylene glycol and the CAS number of the rosin resin is 85026-55-7.
[0024] The method for applying the mixed solder paste to the photovoltaic junction box includes the following specific steps: The rosin resin was heated and dissolved, and then mixed with the solvent, and then mixed with the mixed tin powder, stirred for 10 minutes, and vacuumed for 30 minutes to obtain a molded mixed solder paste; the copper device was wiped with a dust-free cloth, and the obtained mixed solder paste was applied to a steel mesh with an opening of 8mm*4mm and a thickness of 1.10mm for printing. The middle of the steel mesh was concave, and no pressure was applied in an air atmosphere. Soldering was performed at 180°C for 38S and then cooled to room temperature.
[0025] Example 2 The difference between Example 2 and Example 1 is that the Sn in the mixed tin powder raw material 63 Pb 37 Powder and Sn 69.5 Bi 30 Cu 0.5 The mass ratio is 3:1.
[0026] Example 3 The difference between Example 3 and Example 1 is that the Sn in the mixed tin powder raw material 63 Pb 37 Powder and Sn 69.5 Bi 30 Cu 0.5 The mass ratio is 6:1.
[0027] Example 4 The difference between Example 4 and Example 1 is that the tin-bismuth alloy powder in the mixed tin powder raw material is Sn 64 Bi 35 Ag 1 Among them, Sn 64 Bi 35 Ag 1 Sn 64 Bi 35 Ag 1 -T3 type.
[0028] Example 5 The difference between Example 5 and Example 1 is that the application method of the mixed solder paste includes the following specific steps: The rosin resin was heated and dissolved, and then mixed with the solvent, and then mixed with the mixed tin powder, stirred for 10 minutes, and vacuumed for 30 minutes to obtain a molded mixed solder paste; the copper device was wiped with a dust-free cloth, and the obtained mixed solder paste was applied to a steel mesh with an opening of 8mm*4mm and a thickness of 1.10mm for printing. The middle of the steel mesh was concave, and no pressure was applied in an air atmosphere. Soldering was performed at 170°C for 38s and then cooled to room temperature.
[0029] Example 6 The difference between Example 6 and Example 1 is that the method for applying the mixed solder paste includes the following specific steps: The rosin resin was heated and dissolved, and then mixed with the solvent, and then mixed with the mixed tin powder, stirred for 10 minutes, and vacuumed for 30 minutes to obtain a molded mixed solder paste; the copper device was wiped with a dust-free cloth, and the obtained mixed solder paste was applied to a steel mesh with an opening of 8mm*4mm and a thickness of 1.10mm for printing. The middle of the steel mesh was concave, and no pressure was applied in an air atmosphere. Soldering was performed at 200°C for 38S and then cooled to room temperature.
[0030] Example 7 The difference between Example 7 and Example 1 is that the method for applying the mixed solder paste includes the following specific steps: The rosin resin was heated and dissolved, and then mixed with the solvent, and then mixed with the mixed tin powder, stirred for 10 minutes, and vacuumed for 30 minutes to obtain a molded mixed solder paste; the copper device was wiped with a dust-free cloth, and the obtained mixed solder paste was applied to a steel mesh with an opening of 8mm*4mm and a thickness of 1.10mm for printing. The middle of the steel mesh was concave, and no pressure was applied in an air atmosphere. Soldering was performed at 100°C for 23s, then at 150°C for 33s, and then cooled to room temperature.
[0031] Example 8 The difference between Example 8 and Example 1 is that the raw materials of the solder paste in the mixed solder paste include the following raw materials in parts by weight: 45 kg of solvent, 35 kg of rosin resin, 2 kg of hydrogenated castor oil, and 2 kg of fumed silica, wherein the hydrogenated castor oil is PEG40, and the average particle size of the fumed silica is 10-20 nm.
[0032] The application method of the mixed solder paste includes the following specific steps: The rosin resin is heated and dissolved, and then mixed with a solvent, rosin resin, hydrogenated castor oil, and fumed silica, and stirred evenly to form a solder paste. The solder paste is mixed with mixed tin powder, stirred for 10 minutes, and vacuumed for 30 minutes to obtain a molded mixed solder paste. After wiping the copper device with a dust-free cloth, the obtained mixed solder paste is applied to a steel mesh with an opening of 8mm*4mm and a thickness of 1.10mm for printing. The steel mesh is concave in the middle, and no pressure is applied in an air atmosphere. Soldering is performed at 180°C for 38S and then cooled to room temperature.
[0033] Example 9 The difference between Example 9 and Example 8 is that the flux paste raw materials in the mixed solder paste include the following raw materials in parts by weight: 45 kg of solvent, 35 kg of rosin resin, 2 kg of hydrogenated castor oil, 2 kg of fumed silica, and 8 kg of activator; wherein the activator is methylsuccinic acid.
[0034] The application method of the mixed solder paste includes the following specific steps: After the rosin resin is heated and dissolved, it is mixed with a solvent, rosin resin, hydrogenated castor oil, and fumed silica. After stirring evenly, an activator is added and stirred continuously to form a solder paste. The solder paste is mixed with mixed tin powder, stirred for 10 minutes, and vacuumed for 30 minutes to obtain a molded mixed solder paste. After the copper device is wiped with a dust-free cloth, the obtained mixed solder paste is applied to a steel mesh with an opening of 8mm*4mm and a thickness of 1.10mm for printing. The steel mesh is concave in the middle. No pressure is applied in an air atmosphere and soldering is performed at 180°C for 38S, and then cooled to room temperature.
[0035] Example 10 The difference between Example 10 and Example 9 is that the amount of solvent used in the flux paste raw material in the mixed solder paste is 40 kg, the amount of rosin resin used is 40 kg, the amount of hydrogenated castor oil used is 1 kg, the amount of fumed silica used is 3 kg, and the amount of activator used is 5 kg.
[0036] Embodiment 11 The difference between Example 11 and Example 9 is that the amount of solvent used in the flux paste raw material in the mixed solder paste is 50 kg, the amount of rosin resin used is 30 kg, the amount of hydrogenated castor oil used is 3 kg, the amount of fumed silica used is 1 kg, and the amount of activator used is 10 kg.
[0037] Comparative Example Comparative Example 1 The difference between Comparative Example 1 and Example 1 is that the mixed tin powder in the mixed solder paste is Sn 63 Pb 37 pink.
[0038] Comparative Example 2 The difference between Comparative Example 2 and Example 1 is that the mixed tin powder in the mixed solder paste is Sn 42 Bi 58 -T3 parts and Sn 63 Pb 37 -Mixture of T3E powder, Sn 42 Bi 58 -T3 parts and Sn 63 Pb 37 -The mass ratio of T3E powder is 2:5.
[0039] Performance testing After soldering was performed using the mixed solder paste provided in Examples 1-11 and Comparative Examples 1-2 of the present application, the performance of the solder joints was tested. The specific test results are shown in Table 1.
[0040] Detection Methods 1. Appearance inspection Observe and record the height, size and appearance of the solder joint after it is formed.
[0041] 2. Wettability Refer to ICPTM 650 2.4.45 "Solder Paste - Wetting Test" standard to test the wetting performance of the mixed solder paste.
[0042] Table 1: Performance test results data table It can be seen from the performance test results that the present application uses two alloys with large melting point differences to mix and make solder paste, which can make the solder joints hard and firm without deformation, and use the unmelted high-temperature phase to achieve secondary welding with the remaining solder sheet, and firmly weld with the solder strip. The original process of applying solder paste / glue and then sticking the solder sheet is changed by printing the mixed solder paste, which optimizes the process, saves time, and increases efficiency. Through the different processes of the mixed solder paste in the welding process in Examples 5-7, it can be seen from the performance test results that in the low-temperature welding of 170-200°C, the mixed solder paste prepared by the present application is formed into a preformed solder sheet by low-temperature baking by printing, which can improve the strength of the solder sheet, has strong viscosity and is not easy to fall off, and can provide a flux for secondary welding. In Examples 8-11, the raw materials of the flux paste in the mixed solder paste are different, and the comprehensive performance of the mixed solder paste prepared in Example 9 is better.
[0043] By comparing Comparative Examples 1-2 with Example 1, it can be seen that Comparative Example 1 uses Sn 63 Pb 37 The solder powder is used as soldering tin powder. Although the solder joint height is kept within a reasonable range, the solder joint state after low-temperature soldering is relatively soft, and the solder joint is prone to deformation and slag after being bumped. This further illustrates that the use of two different types of tin powder in this application can keep the solder joint hard, firm, stable and reliable. In Comparative Example 2, the mixed tin powder is Sn 42 Bi 58 -T3 parts and Sn 63 Pb 37 -T3E powder mixture, although the solder joint size is moderate and the height is appropriate, the coarse metallographic structure of (2)Bi makes the alloy brittle, affecting the strength of the solder joint. Compared with Example 1, the strength of the solder joint in Comparative Example 2 is lower, and black solder joints appear in Comparative Example 2. 64 Bi 35 Ag 1 As soldering tin powder, the powder can refine the grains, enhance the strength of solder joints, and reduce the generation of black solder joints.
[0044] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A mixed solder paste for photovoltaic junction boxes, characterized in that: The invention comprises a mixed tin powder and a solder paste, wherein the mixed tin powder comprises Sn 63 Pb 37 powder and tin-bismuth alloy powder, wherein the tin-bismuth alloy is Sn 69.5 Bi 30 Cu 0.5 and Sn 64 Bi 35 One of Ag1, the Sn 63 Pb 37 The mass ratio of tin-bismuth alloy powder to tin-bismuth alloy powder is (3-6):
1.
2. The mixed solder paste for photovoltaic junction boxes according to claim 1, characterized in that: The mass ratio of the mixed tin powder to the soldering solder paste is 100:(10-13).
3. The mixed solder paste for photovoltaic junction boxes according to claim 1, characterized in that: The particle size of the tin powder in the mixed tin powder is 25-53 μm.
4. The mixed solder paste for photovoltaic junction boxes according to claim 1, characterized in that: The soldering paste comprises the following raw materials in parts by weight: 40-50 parts of solvent, 30-40 parts of rosin resin, 1-3 parts of hydrogenated castor oil, 1-3 parts of fumed silica and 5-10 parts of activator.
5. The mixed solder paste for photovoltaic junction boxes according to claim 4, characterized in that: The solvent is at least one of polyethylene glycol, ethylene glycol, tetrahydrofurfuryl alcohol, hydrogenated rosin propyl ether and diethyl adipate.
6. The mixed solder paste for photovoltaic junction boxes according to claim 4, characterized in that: The active agent is at least one of methylsuccinic acid, oxalic acid, salicylic acid and succinic acid.
7. A method for applying a mixed solder paste to a photovoltaic junction box according to any one of claims 1 to 6, characterized in that: The method comprises the following specific steps: uniformly mixing the mixed tin powder and the flux paste, vacuumizing and shaping the mixed tin paste, applying the mixed tin paste on the concave substrate for printing, and then soldering at 170-200°C for 35-45s without applying pressure in an air atmosphere, and finally cooling to room temperature.
8. The method for applying the mixed solder paste to a photovoltaic junction box according to claim 7, characterized in that: The method comprises the following specific steps: heating and dissolving rosin resin, then adding solvent, hydrogenated castor oil, fumed silica and activator and mixing them evenly to obtain solder paste; mixing mixed tin powder and solder paste evenly, and forming mixed solder paste after vacuuming; applying the mixed solder paste on a concave substrate for printing, and then soldering at 170-200°C for 35-45s without applying pressure in an air atmosphere, and finally cooling to room temperature.
Citation Information
Patent Citations
Soldering tin paste
CN104827198A
Method for preparing pre-welded copper-clad ceramic substrate through laser cladding
CN111785644A
Solder paste with high electric conductivity and heat conductivity and preparation method thereof
CN115703176A
Automatic tin pasting equipment and automatic tin pasting method for photovoltaic module
CN116100112A
Production process of low-temperature washing solder paste and flux paste
CN117718632A